1998
DOI: 10.1007/s004410051190
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of cGMP in the adrenal gland in the rat, guinea pig and mouse after stimulation with sodium nitroprusside

Abstract: Nitric oxide (NO) acts as an intercellular messenger molecule in the nervous system. In the adrenal gland sympathetic preganglionic fibers innervating the medulla, as well as intrinsic neural ganglion cells, contain nitric oxide synthase (NOS). Nitric oxide stimulates the soluble enzyme guanylate cyclase forming cyclic GMP (cGMP). Using sodium nitroprusside (SNP) as nitric oxide donor we have studied the putative target cells for nitric oxide in the rat adrenal gland, both in vivo and in vitro. The guinea pig … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 84 publications
(90 reference statements)
0
3
0
Order By: Relevance
“…The research of Holmberg et al (1998) on the role of NO in the rat, guinea pig and mouse adrenal indicated that the chromaffin cells (especially the noradrenergic ones) and blood vessels are targets for NO. In trout and in mammals, nitrergic nerves appear to be involved in the control of cellular activity of chromaffin and interrenal cells .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research of Holmberg et al (1998) on the role of NO in the rat, guinea pig and mouse adrenal indicated that the chromaffin cells (especially the noradrenergic ones) and blood vessels are targets for NO. In trout and in mammals, nitrergic nerves appear to be involved in the control of cellular activity of chromaffin and interrenal cells .…”
Section: Discussionmentioning
confidence: 99%
“…This molecule appears to be involved in the regulation of cellular activity of the adrenal gland. In fact, nNOS has been localized in mammalian chromaffin cells and nerve elements (Afework et al, 1992(Afework et al, , 1995Holmberg et al, 1998;Schwarz et al, 1998) and in frog chromaffin cells (Cartier et al, 2001); among fishes, it has been found to be sparsely localized in chromaffin cells and more frequently in nerve elements close to the adrenal homolog in the teleost Oncorhynchus mykiss .…”
Section: Introductionmentioning
confidence: 97%
“…Of interest is that in the thoracic spinal cord, the sympathoexcit- atory effect of NOS I-derived NO is mediated by cyclic guanosine monophosphate (cGMP) (23). Likewise, cGMP signaling in the chromaffin cells, particularly the noradrenergic ones, is the target for NO in the adrenal gland (15). At the same time, we also demonstrated in adrenalectomized rats that whereas the plasma level of norepinephrine returned to baseline after intrathecal administration of SMT, MAP was sustained at a level that was higher than the adrenalectomy-alone group.…”
Section: Discussionmentioning
confidence: 99%